Monsoon variability –climate change - sustainable development with special reference to Andhrapradesh - Rao, V Lakshamana; Sravani, A; Ramakrishna, SSVS (Recent Research in Science and Technology, 2012)
<!--[if gte mso 9]> 800x600 <![endif]--><!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <mce:style><! st1\:*{behavior:url(#ieooui) } --> <!--[endif] --><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman","serif";} --> <!--[endif] --> India is an agricultural country and is also a monsoonal country. There are two Monsoon systems. South West monsoon (summer monsoon) and North East monsoon (winter monsoon) influencing the weather and climate of the country. It is these two monsoons which gives water by way of rainfall and this rainfall results in runoff, infiltration, percolation and deep percolation. Part of it results in storage as ground water and part of it evaporates. This rainfall sustains the water in the lakes and tanks. This replenishes the ground water and raises the water levels in the wells. This rainfall is vital for Agriculture. In order to have sustainable agricultural production, we must know not only the rainfall amount but its variation. The aim and objective of the present article is to analyze the monsoon rainfall and its variation over a long period for the state of Andhra Pradesh. The climatic trends of rainfall and climate change for various stations in Andhra Pradesh have been presented and discussed and steps to sustainable development have been suggested.